2016
DOI: 10.1161/atvbaha.115.306497
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Associates With Human Abdominal Aortic Aneurysm and Rupture

Abstract: Objective Asthma and abdominal aortic aneurysms (AAA) both involve inflammation. It remains unknown whether these diseases interact. Approach and Results Databases analyzed included DNRP: a population-based nationwide case-control study included all patients with ruptured AAA (rAAA) and age- and sex-matched AAA controls without rupture in Denmark from 1996–2012. VIVA: Subgroup study of participants from the population-based randomized Viborg vascular screening trial. Asthmatic patients were categorized by ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Eotaxin was included in our analysis solely on the basis that it formed part of a broad (relatively unbiased) cytokine multiplex panel, and we had no a priori suggestion of a link with AAA. Intriguingly, however, acute asthma has recently been linked to AAA susceptibility and rupture, an observation that appears to indirectly validate our observed eotaxin‐AAA association.…”
Section: Discussionsupporting
confidence: 84%
“…Eotaxin was included in our analysis solely on the basis that it formed part of a broad (relatively unbiased) cytokine multiplex panel, and we had no a priori suggestion of a link with AAA. Intriguingly, however, acute asthma has recently been linked to AAA susceptibility and rupture, an observation that appears to indirectly validate our observed eotaxin‐AAA association.…”
Section: Discussionsupporting
confidence: 84%
“…Since CysLT1 antagonists target both the inflammatory and proteolytic components of AAA pathogenesis, they would represent a drug candidate with a mode of action that has not yet been clinically tested. Furthermore, CysLT1 antagonists, typified by montelukast, are effective medications against human asthma, a disease which is experimentally and epidemiologically associated with AAA and rupture ( 37 , 38 ). It has also been observed that AAA and asthma share several pathophysiological similarities ( 39 , 40 ) and epidemiological data have revealed a positive correlation between use of montelukast and reduced cardiovascular risk in men ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous systematic review and meta-analysis has shown an association between psoriasis and AAA. 13 Recently, retrospective cohort studies using Danish populations reported that psoriasis 14 and asthma 15 were associated with higher risk for AAA.…”
Section: Abdominal Aortic Aneurysmsmentioning
confidence: 99%